Análise da frequência alélica de 15 LOCI STR na população do Rio Grande do Norte - Oliveira, Taissa Maria Moura de (2012)
Human population have a significant number of polymorphic loci, whose use and applications range from construction of linkage maps, to study the evolution of populations, through the determination of paternity, forensic medicine and migration. Currently, STRs (Short Tanden Repeats) markers are considered the major markers for human identification, mainly due to its abundance and high variability because of the fact that they are easily amplifiable by PCR (Polymerase Chain Reaction), work with low amounts of DNA and be capable of automation processes involving fluorescence detection. The creation of regional databases containing allele frequencies of population provide subsidies to increase the reliability of the results of determining the genetic link. This paper aims to obtain a database of allele frequencies of 15 polymorphic molecular loci (D8S1179, D21S11, D7S820, CSF1PO, D19S433, vWA, TPOX, D18S51, D3S1358, TH01, D13S317, D16S539, D2S1338, D5S818 e FGA) in a population classifies as born in the State of Rio Grande do Norte, Brazil, totaling 1100 unrelated individuals. To evaluate the frequency, DNA samples were submitted to PCR amplification, followed by capilarry electrophoresis genetic sequencer. The frequencies identified in this study were compared with brazilian population in general and other states in Brazil. Except for the loci D21S11, D19S433 and D2D1338, the genotypes found were in Hardy-Weinberg equilibrium and no significant differences among the frequencies were found in the populations studied. The most informative loci was D2S1338 and D18S51, and the less informative is the locus TPOX